Forest History—New Perspectives for an Old Discipline - Muigg, Bernhard; Tegel, Willy (Frontiers in Ecology and Evolution, 2021)
The scientific field of forest history studies the development of woodlands and their interrelationship with past human societies. During the last decades, the subject has experienced a constant decrease of importance, reflected in the loss of representation in most universities. After two hundred years of existence, an insufficient theoretical basis and the prevalence of bibliographical and institutional studies on post-medieval periods have isolated the field and hindered interdisciplinary exchange. Here we present possible new perspectives, proposing wider methodological, chronological, thematic, and geographical areas of focus. This paper summarises the development of the field over time and recommends content enhancement, providing a specific example of application from Roman France. Furthermore, we introduce a topical definition of forest history. Following the lead of other fields of the humanities and environmental sciences focussing on the past, forest history has to adapt to using other available archives in addition to historical written sources. In particular, historical and archaeological timber as well as pollen are essential sources for the study of past forests. Research into forest history can substantially add to our understanding of relevant issues like societal responses to climate change and resource scarcity in the past and contribute to future scenarios of sustainability.